Biaxially oriented polyester film and method for producing the same

The method addresses non-uniformity in molecular arrangement and heat shrinkage of two-axis oriented polyester films by using recycled resin and a cooling area in the manufacturing process, resulting in a film suitable for diverse applications with reduced environmental impact.

JP2025016601AActive Publication Date: 2025-02-04TOYOBO CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024189336
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-06-02
Filing Date
2024-10-28
Publication Date
2025-02-04
Estimated Expiration
2041-08-10

AI Technical Summary

Technical Problem

Conventional methods for producing two-axis oriented polyester films using recycled plastic bottles face challenges in maintaining uniform molecular arrangement and minimizing heat shrinkage and distortion in the film width direction, leading to non-uniform physical properties, which hinders their suitability for various processing applications.

Method used

A manufacturing method involving the use of recycled polyester resin, including a cooling area before the heat fixing process, and specific extension conditions to reduce molecular arrangement variations and heat shrinkage in the width direction, ensuring the film meets criteria such as temperature crystallization, angle change, and heat reduction rates.

Benefits of technology

The method produces a two-axis oriented polyester film with reduced molecular arrangement variations and heat shrinkage, making it suitable for various processing applications and environmentally friendly by utilizing recycled materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016601000001_ABST
    Figure 2025016601000001_ABST
Patent Text Reader

Abstract

To provide a biaxially oriented polyester film which has little variation or distortion in molecular orientation and thermal shrinkage rate in a film width direction and has uniform physical properties, making it suitable for various processing applications and which is also environmentally friendly, and a method for producing the same.SOLUTION: A biaxially oriented polyester film made of a polyester resin composition containing polyester resin and particles made from recycled PET bottles satisfies all of the following requirements (1) to (4). (1) A crystallization temperature upon heating is 120°C or higher and 139°C or lower. (2) An amount of change in orientation angle in a width direction of the film is between 0° and 10° per 0.5 m. (3) When heat-treated at 150°C for 30 minutes, a thermal shrinkage rate across an entire width of the film is 0.5% to 2.0% in a longitudinal direction and -1.0% to 1.0% in a transverse direction. (4) A content of an isophthalic acid component relative to 100 mol % of all dicarboxylic acid components in the polyester resin composition is 0.01 mol % or more and 3.0 mol % or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a biaxially oriented polyester film and a manufacturing method thereof, and more particularly to a biaxially oriented polyester film which is suitable for various processing applications due to its small variation and distortion in molecular orientation and thermal shrinkage rate in the width direction of the film and its uniform physical properties in the width direction of the film, and which is environmentally friendly because it uses polyester resin recycled from the market and society, including PET bottles (hereinafter, may be referred to as "polyester resin made from recycled PET bottles"), and a manufacturing method thereof. [Background technology]

[0002] Polyester resins such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), which are thermoplastic resins with excellent heat resistance and mechanical properties, are used in a wide variety of fields, including plastic films, electronics, energy, packaging materials, automobiles, etc. Among plastic films, biaxially oriented polyester films are widely used in industrial and packaging fields because they offer an excellent balance between mechanical strength, heat resistance, dimensional stability, chemical resistance, optical properties, and cost.

[0003] In recent years, with the growing demand for a recycling-oriented society, the use of recycled raw materials has been promoted in the field of materials. For the aforementioned polyester resin, used PET beverage bottles are recycled, and the method of utilizing them is attracting attention. It is said that using recycled PET bottle materials leads to a reduction in CO2 emissions, and from the perspective of the global environment, there is a desire to increase the proportion of recycled PET bottle materials used even if only slightly.

[0004] In recent years, secondary processing steps such as coating, printing, and deposition of polyester films have been increasing in speed and widening and lengthening of the substrate film in order to improve productivity. In particular, when the film is widened, the effects of heat and tension during processing become greater, making it difficult to uniformize the physical properties in the width direction, and it is difficult to obtain a biaxially oriented polyester film suitable for various processing applications. In particular, there is a demand for reducing the variation in molecular orientation and heat shrinkage rate and distortion in the film width direction.

[0005] For example, Patent Document 1 discloses a biaxially oriented polyethylene terephthalate film made from recycled PET bottles. This technology makes it possible to obtain a biaxially oriented polyester film that has excellent thermal stability, little residual components of the cleaning solution used in producing recycled PET bottle raw materials, little foreign matter, and stable resistivity when melted, without compromising the productivity and quality of the film.

[0006] However, although there is mention of a biaxially oriented polyethylene terephthalate film using recycled PET bottle materials and an alkaline washing method for obtaining a film with excellent thermal stability and little foreign matter, there is no mention of molecular orientation in the width direction of the film or variation in heat shrinkage rate or distortion. In addition, in order to obtain a biaxially oriented polyethylene terephthalate film using recycled PET bottle materials, a method has been proposed in which recycled PET bottle materials are mixed with polyester resin derived from fossil fuels, and the melt-extruded unstretched sheet is heated to 100°C with a group of heated rolls and an infrared heater, stretched 4.0 times in the longitudinal direction with a group of rolls, and then stretched 4.2 times in the width direction at 130°C, followed by heat setting treatment and further heat relaxation treatment. However, the inventors found that polyester resins made from recycled PET bottles are generally recycled polyester resins that have been subjected to processes such as crushing collected used PET bottles, removing foreign matter by washing, and decontamination by high-temperature treatment, and that the temperature-induced crystallization temperature is usually about 130° C., which is lower than the temperature-induced crystallization temperature of polyester resins derived from fossil fuels, and therefore the resins are prone to break during stretching at stretching temperatures higher than 130° C. On the other hand, if the stretching temperature is lowered to prevent breakage during stretching, a difference in the longitudinal stretching stress caused by stretching in the width direction is likely to occur between the ends held by the clips and the central portion where the restraining force is relatively small, and a bowing phenomenon occurs in which the physical properties are non-uniform in the width direction of the film, and the molecular orientation and heat shrinkage rate in the width direction of the film and distortion are likely to occur.

[0007] The bowing phenomenon, when considered geometrically, is a phenomenon in which a straight line drawn across the width of the film at the entrance of the tenter changes to a bow-like curve at the center of the film at the exit of the tenter. The obtained biaxially oriented polyester film has a principal axis of molecular chain orientation that is inclined from the center to the ends, which results in variations and distortion in the width direction in heat shrinkage characteristics, etc., which are thought to be due to differences in the effects of the stretching stress in the longitudinal direction of the film, the shrinkage stress in the longitudinal direction generated in the heat setting process, and the tension generated in the tenter.

[0008] Various measures to reduce the bowing phenomenon have been studied so far. For example, Patent Document 2 proposes a method of appropriately combining film-forming conditions such as longitudinal and transverse stretching conditions, heat setting conditions, and heat relaxation conditions, in which an unstretched sheet is heated with an infrared heater so that both ends of the sheet are at a temperature +3°C higher than the center, and the sheet is stretched in two stages (total stretch ratio 4.0 times) at a stretching temperature of 115°C, with a first stage being 1.4 times and a second stage being 2.86 times, and then the sheet is stretched in the transverse direction at a stretching temperature of 115°C and a stretch ratio of 4.3 times, heat-set at 235°C, and heat-relaxed by 5% in the transverse direction to reduce the difference in physical properties in the transverse direction of the film. However, in order to reduce the difference in physical properties in the width direction of the film, a method of stretching in the longitudinal direction in multiple stages between multiple rolls is used, but the production equipment becomes large-scale, which is disadvantageous in terms of production costs, and there are cases where scratches with the rolls occur and the quality of the biaxially oriented polyester film is impaired, and these issues have not been fully considered. In addition, a polyester film that is suitable for various processing applications because it has little variation and distortion in molecular orientation and heat shrinkage rate in the width direction of the film and has uniform physical properties in the width direction of the film, and is environmentally friendly because it uses polyester resin recycled from PET bottles, has not yet been realized. The inventors have found through their investigations that simply applying the production conditions described in Patent Document 2 to produce the film described in Patent Document 1 does not provide an effect of sufficiently reducing the bowing phenomenon. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent No. 6036099 [Patent Document 2] Patent No. 6070842 Summary of the Invention [Problem to be solved by the invention]

[0010] The object of the present invention is to improve the problems of the conventional technology and to provide an environmentally friendly biaxially oriented polyester film and a manufacturing method thereof, which uses polyester resin made from recycled PET bottles, has little variation in molecular orientation and thermal shrinkage rate and distortion in the width direction of the film, and has uniform physical properties in the width direction of the film, making it suitable for a variety of processing applications. [Means for solving the problem]

[0011] As a result of intensive research, the present inventors have found that in a biaxially oriented polyester film obtained by biaxially stretching a polyester resin composition in which a polyester resin made from recycled PET bottles is blended with a polyester resin containing particles, in the process of heating a melt-extruded unstretched sheet and biaxially stretching it, after stretching in the longitudinal direction, it is stretched in the width direction in a tenter, and a cooling region is provided before the heat setting region, and heat setting and heat relaxation treatments are performed, whereby it is possible to obtain a biaxially oriented polyester film that uses polyester resin made from recycled PET bottles, has little variation in molecular orientation and heat shrinkage rate and distortion in the film width direction, and has uniform physical properties in the film width direction, making it suitable for a variety of processing applications and is environmentally friendly.

[0012] That is, the present invention comprises the following: 1. A biaxially oriented polyester film made of a polyester resin composition containing polyester resin and particles made from recycled PET bottles, which satisfies all of the following requirements (1) to (4). (1) The temperature-rising crystallization temperature measured by a differential scanning calorimeter (DSC) is 120° C. or higher and 139° C. or lower. (2) The change in orientation angle in the width direction of the film is from 0° to 10° per 0.5 m. (3) When heat-treated at 150°C for 30 minutes across the entire width of the film, the thermal shrinkage is in the range of 0.5% to 2.0% in the longitudinal direction and -1.0% to 1.0% in the transverse direction. (4) The content of the isophthalic acid component relative to 100 mol % of all dicarboxylic acid components in the polyester resin composition is 0.01 mol % or more and 3.0 mol % or less. Here, the sample collection positions in requirements (2) and (3) shall be the center position across the entire width and positions spaced at intervals of 500 mm from the center position toward both ends. If it is not possible to ensure 500 mm intervals near both ends, samples shall be collected at the end positions where samples can be collected. In addition, requirement (2) requires that the maximum and minimum values ​​of each measurement position data be within a range, and requirement (3) requires that the maximum value of each amount of change between two adjacent sample collection positions be within a range.

[0013] 2. The biaxially oriented polyester film described in 1., characterized in that the content of polyester resin recycled from PET bottles in the polyester resin composition constituting the biaxially oriented polyester film is 50% by mass or more and 100% by mass or less.

[0014] 3. The biaxially oriented polyester film according to 1 or 2 above, wherein the polyester resin made from recycled PET bottles is a mechanically recycled polyester resin and / or a chemically recycled polyester resin.

[0015] 4. A method for producing a biaxially oriented polyester film, comprising a polyester raw material resin melt extrusion process, a biaxial stretching process, a heat setting process, a heat relaxation process, and a process for winding up the biaxially oriented polyester film into a roll, characterized in that in the biaxial stretching process, after stretching in the longitudinal direction, the film is stretched in the width direction in a tenter, and a cooling zone is provided before the heat setting zone. Effect of the Invention

[0016] The present invention can provide an environmentally friendly polyester film and a method for producing the same, which use polyester resin made from recycled PET bottles, have little variation or distortion in molecular orientation and thermal shrinkage rate in the width direction of the film, and have uniform physical properties in the width direction of the film, making them suitable for a variety of processing applications. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a plan view illustrating an example of a biaxial stretching step (tenter apparatus) and a heat setting treatment step for producing the biaxially oriented polyester film of the present invention. [Diagram 2] FIG. 1 is a plan view for illustrating the biaxial stretching step (tenter apparatus) and the heat setting treatment step in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The present invention will be described in detail below. [Polyester resin made from recycled PET bottles] The biaxially oriented polyester film of the present invention preferably uses a polyester resin made from recycled PET bottles, as described below. By using a polyester resin made from recycled PET bottles, the ratio of recycled materials in the film can be increased, making it possible to obtain an environmentally friendly film. As the polyester resin in the present invention made by recycling PET bottles, either a polyester resin obtained by a physical regeneration method in which used PET bottles collected from the market or society are sorted, crushed, and washed to thoroughly remove surface dirt and foreign matter, and then exposed to high temperatures to thoroughly wash away contaminants remaining inside the resin, and then the bottles are pelletized again (hereinafter, this may be referred to as a mechanically recycled polyester resin) or a polyester resin obtained by decomposing polyester resin contained in used packaging containers to the monomer level, removing contaminants, and polymerizing the decomposed resin again (hereinafter, this may be referred to as a chemically recycled polyester resin) can be suitably used.

[0019] The polyester resin used in the biaxially oriented polyester film of the present invention, which is made from recycled PET bottles, is mainly made from recycled containers mainly made of polyethylene terephthalate. For example, recycled beverage containers for tea drinks, soft drinks, etc. can be preferably used. The polyester resin may be appropriately oriented, and is preferably colorless, but may contain a small amount of coloring components.

[0020] The recycled raw materials recycled from the market or society, including PET bottles, which can be preferably used, are polyesters manufactured and molded by normal polymerization and solid-phase polymerization, preferably mainly composed of polyethylene terephthalate, and may contain other polyester components and copolymer components. They may contain metal compounds such as antimony, germanium, and titanium as catalysts, and phosphorus compounds as stabilizers. Germanium is often used as a catalyst in polyesters for PET bottles, and if a film is made using recycled PET bottle raw materials, the film will contain 1 ppm or more of germanium. However, since it is only the catalyst content, it is usually 100 ppm or less, and usually 50 ppm or less.

[0021] Hereinafter, mechanically recycled polyester resin and chemically recycled polyester resin will be described.

[0022] [Mechanically recycled polyester resin] The collected used recycled PET bottles are sorted to avoid mixing with other materials or garbage, and after removing the labels, they are crushed into flakes. These flakes often contain foreign matter attached to them. In addition, it is possible that consumers fill used PET bottles with chemicals such as medicines and solvents and use them. For example, detergents for dishes, insecticides, herbicides, agricultural chemicals, and various oils are possible. Since normal washing cannot sufficiently remove the chemicals adsorbed on the surface of the PET bottles, it is preferable to perform alkaline washing. As the alkali metal hydroxide solution used in this washing process, a sodium hydroxide solution or a potassium hydroxide solution is used. In such a washing process, a preliminary washing may be performed before the alkaline washing. If alkaline washing is not performed, these will remain as foreign matter in the raw resin, which will not only cause contamination and lead to breakage during film production and reduce productivity, but will also remain as foreign matter in the film, affecting the appearance of the film and causing printing defects in the subsequent printing process.

[0023] The concentration of the aqueous solution of alkali metal hydroxide used in the washing step varies depending on the temperature, time, and stirring state, but is usually in the range of 1 to 10% by weight. The time required for washing is in the range of 10 to 100 minutes, and it is preferable to carry out the washing with stirring to enhance the effect.

[0024] It is preferable to perform rinsing and drying after the alkali washing. The alkali washing and rinsing may be repeated several times. If the aqueous solution of alkali metal hydroxide used in the washing in the alkali washing step remains in the flakes, the properties of the film finally obtained may be affected by the subsequent melt extrusion step in the pelletizing step or the melt extrusion step during film formation.

[0025] The sodium and potassium concentrations in the film finally obtained using the polyester resin recycled from these PET bottles are preferably more than 0 ppm and not more than 150 ppm, more preferably 3 to 120 ppm, and even more preferably 5 to 80 ppm. If the sodium or potassium concentration in the film is higher than 150 ppm, the film's heat resistance and thermal stability will decrease and it will become discolored, which is not preferable. If there is no sodium or potassium at all, the effect of suppressing the production of diethylene glycol will be reduced, which is also not preferable. In addition, polyester resin recycled from PET bottles may contain a small amount of these components, and it is difficult to completely eliminate them.

[0026] In such a washing process, the PET bottle flakes are partially hydrolyzed by the aqueous solution of alkali metal hydroxide. In addition, the degree of polymerization of the resin decreases due to the heating during the molding of the PET bottles. Furthermore, after the collected PET bottles are crushed for reuse, the degree of polymerization decreases due to the influence of heat and moisture when melting and pelletizing again. They can be reused as they are, but depending on the application, if the degree of polymerization decreases, the moldability, strength, transparency, heat resistance, etc. may be deteriorated, and they may not be able to be reused as they are.

[0027] In such a case, in order to restore the reduced degree of polymerization, it is preferable to perform solid-state polymerization on the crushed and washed PET bottle flakes or on the flakes which have been melted and pelletized.

[0028] In the solid-state polymerization step, the washed flakes, or the flakes melt-extruded and pelletized, can be subjected to continuous solid-state polymerization in an inert gas such as nitrogen gas or a rare gas at 180 to 245°C, preferably 200 to 240°C.

[0029] It is desirable to adjust the flake or pellet conditions so that the final polyester resin made from recycled PET bottles has an intrinsic viscosity of 0.55 to 0.90 dl / g, preferably 0.60 to 0.85 dl / g.

[0030] The process for pelletizing the flakes will now be described. The flakes are melted, extruded, cooled, and pelletized using an extruder having a degassing means and a filtering means.

[0031] The melting step in the extruder can be carried out by melt kneading at a temperature of usually 260 to 300°C, preferably 265 to 295°C. The flakes obtained by crushing the PET bottles to be fed must be sufficiently dried, and it is preferable to dry them under conditions where the moisture content is 5 to 200, preferably 10 to 100 ppm, and further 15 to 50 ppm. If the flakes contain a large amount of moisture, a hydrolysis reaction will proceed in the melting step, and the intrinsic viscosity of the resulting polyester resin will decrease. As a degassing means, it is preferable to have at least one vacuum vent in the melting zone of the resin.

[0032] The extruder preferably has a filter as a filtering means capable of filtering out solid foreign matter having a particle size of 25 μm or more, preferably 15 μm or more, more preferably 10 μm or more, from the molten resin.

[0033] The molten resin that has passed through the filter passes through a die and is cooled in water, after which it is cut into pellets of the desired shape and granulated.

[0034] [Chemically recycled polyester resin] The method for producing the chemically recycled polyester resin used in the present invention is not particularly limited, but specifically, for example, as described in JP-A-2000-169623, collected used PET bottles are sorted, crushed, washed to remove foreign matter, and then depolymerized to decompose them into raw materials or intermediate raw materials for PET resin, which are then purified and polymerized to produce new PET resin. Depolymerization includes a method in which ethylene glycol (EG) is added in the presence of a catalyst to return the intermediate raw material in resin production to bis-2-hydroxyethyl terephthalate (BHET), which is an intermediate raw material, and then purified and repolymerized into PET, and a method in which polyethylene terephthalate is heated in a non-aqueous organic solvent in the presence of a catalyst containing oxidized iron as an essential component to produce terephthalic acid and ethylene glycol, which are then polymerized again, as described in JP-A-2000-302707. The characteristic of chemically recycled polyester resin is that foreign matter and other materials are removed during the depolymerization / repolymerization process, allowing it to be regenerated into a polyester resin of the same high quality as virgin resin. This makes it more hygienic than the mechanically recycled polyester resin described above, making it particularly suitable for use in food packaging.

[0035] The chemically recycled polyester resin used in the present invention is made from bales of compressed used PET bottles. These PET bottle bales are produced by a known method currently adopted by municipalities. Other polyethylene terephthalate waste and PET bottle flakes can be used as starting materials instead of PET bottle bales.

[0036] A PET bottle bale made by compressing PET bottle waste to reduce its volume is placed in a crusher, and hot water, room temperature water, or hot water or room temperature water containing detergent is poured in to crush the PET bottles underwater.

[0037] Next, the mixture of flakes of PET bottles and washing water discharged from the crusher is immediately subjected to gravity separation to separate the metal, stone, glass, sand and flakes.The flakes are then separated from the washing water, rinsed with ion-exchanged water and centrifuged for dehydration.

[0038] The crude polyethylene terephthalate flakes obtained in the above pretreatment step are depolymerized, melted and simultaneously hydrolyzed to give a polyethylene terephthalate melt with a low degree of polymerization, which is then depolymerized with an excess of ethylene glycol to give a two-component mixed solution of crude BHET and crude ethylene glycol.

[0039] After the depolymerization reaction is completed, the temperature of the mixture of crude BHET and crude ethylene glycol is lowered and the mixture is filtered to remove unreacted linear and cyclic oligomers as high melting point precipitates, coagulation of remaining foreign plastics other than polyethylene terephthalate, and solid foreign matter such as metals. The mixture is then subjected to adsorption and ion exchange treatment to remove colored matter and dissolved ions, thereby removing the foreign matter contained in the crude BHET.

[0040] The mixed solution of crude BHET and crude ethylene glycol obtained through the pre-purification step is subjected to distillation and evaporation operations to separate and distill off ethylene glycol to obtain concentrated BHET, or the mixed solution of the two is cooled to 10°C or less to crystallize BHET, and then the ethylene glycol and BHET are subjected to solid-liquid separation to obtain concentrated BHET, and this concentrated BHET is evaporated in vacuum at a temperature of more than 190°C and not more than 250°C at a residence time of the concentrated BHET in an evaporator of 10 minutes or less to obtain purified bis-β-hydroxyethyl terephthalate.

[0041] After the high purity purified BHET is obtained as described above, the purified BHET is charged into a melt polycondensation reactor to obtain a high purity polyethylene terephthalate polymer.

[0042] [Polyester resin composition] The biaxially oriented polyester film of the present invention is made of a polyester resin composition containing the following polyester resin as a main component. The polyester resin constituting the biaxially oriented polyester film of the present invention is a polymer synthesized from a dicarboxylic acid or its ester-forming derivative and a diol or its ester-forming derivative. Examples include polyethylene terephthalate, polybutylene terephthalate, and polyethylene-2,6-naphthalate, and polyethylene terephthalate is preferred from the viewpoints of mechanical properties, heat resistance, cost, etc. The term "main component" as used herein means that the content in the polyester resin composition is 80% by weight or more, preferably 90% by weight or more, more preferably 95% by weight or more, and most preferably 98% by weight or more.

[0043] In addition, these polyester resins may be copolymerized with other components as long as the object of the present invention is not impaired. Specifically, the copolymerization components include dicarboxylic acid components such as isophthalic acid, naphthalenedicarboxylic acid, 4,4-diphenyldicarboxylic acid, adipic acid, sebacic acid and their ester-forming derivatives. In addition, the diol components include diethylene glycol, hexamethylene glycol, neopentyl glycol, and cyclohexanedimethanol. In addition, polyoxyalkylene glycols such as polyethylene glycol and polypropylene glycol are also included. The copolymerization amount is preferably 10 mol% or less per constituent repeating unit, more preferably 5 mol% or less, and most preferably 3 mol% or less.

[0044] Among the polyester resins constituting the biaxially oriented polyester film of the present invention, examples of a method for producing a polyester resin derived from a fossil fuel other than a mechanically recycled polyester resin or a chemically recycled polyester resin include a method in which the above-mentioned dicarboxylic acid or its ester-forming derivative and a diol or its ester-forming derivative are used as main starting materials, and the resulting polyester resin is then subjected to an esterification or ester exchange reaction according to a conventional method, and then subjected to a polycondensation reaction at high temperature and reduced pressure.

[0045] The intrinsic viscosity of the polyester resin constituting the biaxially oriented polyester film of the present invention is preferably in the range of 0.50 to 0.90 dl / g, more preferably 0.55 to 0.80 dl / g, from the viewpoints of film formability and recollection.

[0046] The polyester resin composition of the present invention preferably contains at least one type of particles selected from the group consisting of inorganic particles, organic particles, and mixtures thereof.

[0047] Examples of inorganic particles used include particles made of silica (silicon oxide), alumina (aluminum oxide), titanium dioxide, calcium carbonate, kaolin, crystalline glass filler, kaolin, talc, alumina, silica-alumina composite oxide particles, and barium sulfate. Examples of organic particles include acrylic resin particles, melamine resin particles, silicone resin particles, and particles made of crosslinked polystyrene. Among these, particles made of silica (silicon oxide), calcium carbonate, or alumina (aluminum oxide), or particles made of polymethacrylate, polymethyl acrylate, or derivatives thereof are preferred, and particles made of silica (silicon oxide) or calcium carbonate are more preferred, and among these, silica (silicon oxide) is particularly preferred in terms of reducing haze.

[0048] The weight average particle size of the particles in the present invention is a value measured by a call counter, and is preferably 0.5 to 4.0 μm, more preferably 0.8 to 3.8 μm, and further preferably 1.5 to 3.0 μm. If the weight-average particle size of the particles is less than 0.5 μm, the formation of surface irregularities will be insufficient, the slipperiness of the film will decrease, and the air entrained during winding onto a roll will not be uniformly removed, resulting in poor appearance such as wrinkles and pimples on the air bubbles, and the winding properties will be easily deteriorated. If the weight average particle size of the particles exceeds 4.0 μm, the formation of coarse protrusions tends to impair the quality of the film, such as causing printing defects.

[0049] Furthermore, the polyester resin composition of the present invention may contain small amounts of other polymers, antioxidants, heat stabilizers, antistatic agents, ultraviolet absorbers, plasticizers, pigments, or other additives, within the scope of not impairing the object of the present invention.

[0050] The biaxially oriented polyester film obtained as described above preferably contains an isophthalic acid component in the range of 0.01 mol% to 3.0 mol% based on 100 mol% of all dicarboxylic acid components in the film. In general, the crystallinity of polyesters used in PET bottles is controlled to improve the appearance of the bottles, and as a means for this, polyesters containing 10 mol% or less of isophthalic acid components are sometimes used. Therefore, the biaxially oriented polyester film of the present invention contains a certain amount of a material containing an isophthalic acid component.

[0051] The lower limit of the amount of isophthalic acid component in the total dicarboxylic acid components constituting the polyester resin contained in the film is preferably 0.01 mol%, more preferably 0.05 mol%, even more preferably 0.1 mol%, and particularly preferably 0.15 mol%. As mentioned above, polyester resins recycled from the market or society, including PET bottles, contain a large amount of isophthalic acid components, so if the isophthalic acid component constituting the polyester resin in the film is less than 0.01 mol%, it becomes difficult to manufacture a polyester film with a high ratio of recycled resin, which is not very preferable. The upper limit of the amount of isophthalic acid component in the total dicarboxylic acid components constituting the polyester resin contained in the film is preferably 3.0 mol%, more preferably 2.5 mol%, and even more preferably 2.0 mol%. If it exceeds 3.0 mol%, the crystallinity decreases, so the mechanical strength of the film may decrease, which is not very preferable.

[0052] The upper limit of the limiting viscosity of the polyester resin recycled from PET bottles is preferably 0.90 dl / g, more preferably 0.80 dl / g, further preferably 0.75 dl / g, and particularly preferably 0.69 dl / g. If it exceeds 0.90 dl / g, it becomes difficult to extrude the resin from the extruder, which may reduce productivity, and is not preferred.

[0053] In the biaxially oriented polyester film of the present invention, the lower limit of the content of polyester resin recycled from PET bottles relative to the total amount of polyester resin constituting the film is preferably 50% by weight, more preferably 70% by weight, even more preferably 90% by weight, and particularly preferably 100% by weight. If it is less than 50% by weight, the content is poor as a utilization of recycled resin, and is not very preferable in terms of contribution to environmental protection. In addition, polyester resin recycled from PET bottles can also be used as a master batch (high-concentration resin) used when adding lubricants and additives such as inorganic particles to improve the function of the film.

[0054] [Method of manufacturing biaxially oriented polyester film and film roll] The biaxially oriented polyester film of the present invention can be obtained, for example, by supplying and mixing polyester resin chips made from recycled PET bottles as described above and chips of a polyester resin composition mainly composed of polyester resin to an extruder equipped with a hopper, melt-extruding the chips using the extruder to form an unstretched sheet, and stretching the unstretched PET sheet. Preferred examples are given below, but the present invention is not limited to these.

[0055] The biaxially oriented polyester film of the present invention may have a single layer, two layers, three layers, or a laminated structure of four or more layers. In the case of a two-layer or more layer structure, each layer contains the polyester resin, inorganic particles, and a resin other than the polyester resin as described above as constituent components, but the type or content of any of the constituent components of each adjacent layer is different. In the case of a single-layer structure, the surface layer (A) in the present invention corresponds to the entire biaxially oriented polyester film. In the case of a two-layer structure, the surface layer (A) in the present invention is one or both layers. In the case of a three-layer structure, the surface layer (A) in the present invention is one or both layers.

[0056] In the case of a three-layer structure, if the compositions constituting the film are represented as A, A', B, and C, the film can have a structure of, for example, A / B / C, A / B / A, or A / B / A', but if there is no need to change the surface characteristics of both sides, it is easier to manufacture and preferable to have an A / B / A structure in which both sides are designed to have the same composition. Here, A and A' do not have the same composition.

[0057] In particular, in the case of a three-layer structure, even if there are no inorganic particles in the base layer (B), the surface roughness of the film can be controlled by controlling the amount of added particles only in the surface layer (A), and the content of inorganic particles in the film can be reduced, which is preferable. This is because it also improves the problem of odor components escaping through voids (spaces) formed at the boundary between the inorganic particles and the polyester resin, which reduces the aroma retention. Furthermore, as long as it does not adversely affect the properties of the film surface, it is easy to mix and use recovered raw materials from the edges generated during the film production process or recycled raw materials from other film production processes in the base layer (B), which is also advantageous in terms of cost.

[0058] As described above, when the film has a two-layer structure or more, the chemically recycled polyester resin and the mechanically recycled polyester resin can be laminated as separate layers. For example, in the case of a three-layer structure of A / B / A, by disposing a chemically recycled polyester resin in the outermost layer A and a mechanically recycled polyester resin in the central layer B, it is possible to reduce defects in the film by having the chemically recycled polyester resin with fewer impurities in the surface layer. On the other hand, by disposing a mechanically recycled polyester resin in the outermost layer A and a chemically recycled polyester resin in the central layer B, it is possible to improve adhesion with sealants, etc. by having the mechanically recycled polyester resin with a high isophthalic acid content in the surface layer side.

[0059] The lower limit of the particle content in the surface layer (A) of the biaxially oriented polyester film of the present invention is 500 ppm by weight, more preferably 600 ppm by weight, and particularly preferably 700 ppm by weight. If the particle content is less than 500 ppm by weight, the slipperiness and winding property of the film surface may decrease, which is not preferable.

[0060] The content of inorganic particles in all layers of the biaxially oriented polyester film of the present invention is preferably 100 ppm or more and 1000 ppm or less, more preferably 800 ppm or less. If the content of inorganic particles is less than 100 ppm, the slipperiness is reduced, which causes problems during roll running, winding, rewinding, slitting, etc. during the film manufacturing process, and is likely to cause scratches on the film surface, winding wrinkles, and static electricity. If the content of inorganic particles exceeds 1000 ppm, the arithmetic mean height Sa and maximum protrusion height Sp of the film surface tend to be high, so care must be taken. In addition, the number of voids in the film increases, which is likely to cause a decrease in transparency.

[0061] When the polyester resin and polyester resin composition recycled from PET bottles are melt-extruded, it is preferable to dry them using a dryer such as a hopper dryer or a paddle dryer, or a vacuum dryer. After drying the polyester resin and polyester resin composition recycled from PET bottles, the polyester resin is melted at a temperature of 200 to 300°C or higher and extruded into a film using an extruder. Alternatively, the polyester resin, particles, and additives as necessary may be sent out by separate extruders, merged, mixed, melted, and extruded into a sheet. When extruding the molten resin composition, any existing method such as a T-die method or a tubular method can be used.

[0062] The extruded sheet-like molten polyester resin can be quenched to obtain an unoriented sheet. As a method for quenching the molten polyester resin, a method in which the molten polyester resin is cast onto a rotating drum from a die and quenched and solidified to obtain a substantially unoriented resin sheet can be suitably adopted. The temperature of the rotating drum is preferably set to 40° C. or lower.

[0063] Furthermore, the unstretched sheet obtained can be subjected to a combination of processes such as a biaxial stretching process in the longitudinal direction and the width direction, a heat setting process, and a heat relaxation process as described below to obtain the biaxially oriented polyester film of the present invention. The details are explained below. The longitudinal direction means the direction in which the unstretched sheet runs, and the width direction means the direction perpendicular thereto.

[0064] The stretching method may be simultaneous biaxial stretching, in which stretching in the longitudinal direction and the width direction is performed simultaneously, or sequential biaxial stretching, in which stretching in either the longitudinal direction or the width direction is performed first. However, sequential biaxial stretching is most preferred from the viewpoints of a fast film-forming speed and high productivity, and of excellent thickness uniformity of the finally obtained biaxially oriented polyester film. The film-forming speed referred to here means the running speed (m / min) of the biaxially oriented polyester film when it is taken up around a master roll after the stretching step.

[0065] The temperature during stretching of the unstretched sheet in the longitudinal direction is preferably in the range of 80 to 130° C., and the stretch ratio is preferably in the range of 3.3 to 4.7 times. When the stretching temperature is 80°C or higher and the stretching ratio is 4.7 times or less, the shrinkage stress in the longitudinal direction is reduced, the bowing phenomenon is reduced, and the molecular orientation and thermal shrinkage rate variation and distortion in the width direction of the obtained biaxially oriented polyester film are reduced, which is preferable.

[0066] Furthermore, when stretching an unstretched sheet in the longitudinal direction, a method of stretching by heating using an infrared heater or the like is preferred over a method of stretching in multiple stages between multiple rolls in terms of the scale of the production equipment, manufacturing costs, and damage defects such as adhesive damage and transfer damage caused by rolls, as this method makes it easy to obtain high temperatures, facilitates localized heating, and reduces damage defects caused by rolls.

[0067] The film obtained by stretching the unstretched sheet in the longitudinal direction may be subjected to a surface treatment such as corona treatment or plasma treatment as necessary, and then a resin dispersion or resin solution may be applied to at least one surface of the film to impart functions such as easy slippage, easy adhesion, and antistatic properties.

[0068] When the film obtained by stretching an unstretched sheet in the longitudinal direction is to be stretched in the width direction, the film is introduced into a tenter device, both ends of the film obtained by stretching the unstretched sheet in the longitudinal direction are held with clips, and the film is heated to a predetermined temperature with hot air. After that, the film is transported in the longitudinal direction while the distance between the clips is increased, thereby stretching the film in the width direction.

[0069] In the biaxially oriented polyester film of the present invention, the temperature-raised crystallization temperature of the polyester resin recycled from PET bottles relative to the total amount of polyester resin constituting the film is usually about 130° C., and therefore the film is prone to breakage during stretching at a stretching temperature higher than 130° C. Furthermore, if the stretching temperature is lowered to prevent breakage during stretching, a difference in the longitudinal stretching stress caused by stretching in the width direction is likely to occur between the ends held by the clips and the central part where the restraining force is relatively small, causing a bowing phenomenon in which physical properties become non-uniform in the width direction of the film, and making it prone to variations in molecular orientation and thermal shrinkage and distortion in the width direction of the film.

[0070] In order to improve the non-uniformity of physical properties in the width direction of the film caused by the breakage and bowing phenomenon during stretching, it is preferable in the present invention to stretch the film in the longitudinal direction in the biaxial stretching step, then stretch the film in the width direction in a tenter, and provide a cooling zone before the heat setting zone. The cooling zone before the heat setting zone refers to a cooling step in which the temperature of the film stretched in the width direction is lowered after the film is stretched in the tenter in the width direction, for example, by blocking the hot air of the heating zone with a shielding plate such as an aluminum plate inside the tenter before the heat setting zone, or by blocking the hot air and actively feeding compressed air therein. The temperature of the film in the cooling region is preferably equal to or lower than the glass transition temperature (Tg) of the film. When the film is stretched in the width direction in the tenter, the central portion has a relatively small restraining force compared to the ends held by the clips, so deformation due to the longitudinal stretching stress caused by the width direction stretching and the longitudinal shrinkage stress caused by the heat setting treatment becomes large, and the bowing phenomenon is likely to increase, but by cooling the film to a temperature equal to or lower than the glass transition temperature, the rigidity of the film is increased, the deformation of the film is suppressed, and the variation and distortion of the molecular orientation and heat shrinkage rate in the width direction of the film caused by the bowing phenomenon are reduced, which is preferable. The temperature in the cooling region is preferably 60° C. or higher. By cooling the film to a temperature of 55° C. or higher, the thermal shrinkage rate of the film in the longitudinal and transverse directions can be suppressed, which is preferable.

[0071] The preheating temperature during stretching in the width direction is preferably in the range of 100° C. to 130° C. When the preheating temperature during stretching is 100° C. or higher, the shrinkage stress generated during stretching in the longitudinal direction is reduced, the bowing phenomenon is reduced, and the molecular orientation and thermal shrinkage rate variations and distortion in the width direction of the obtained biaxially oriented polyester film are reduced, which is preferable. The temperature during widthwise stretching is preferably in the range of 105°C to 135°C. When the stretching temperature is 105°C or higher, the longitudinal stretching stress caused by the widthwise stretching is reduced, and the bowing phenomenon is less likely to increase, which is preferable. In addition, when the stretching temperature is 135°C or lower, even if a polyester resin recycled from a PET bottle having a temperature-rise crystallization temperature of about 130°C is used, breakage during stretching is less likely to occur, which is preferable. The stretching ratio in the width direction is preferably in the range of 3.5 to 5.0 times. When the stretching ratio in the width direction is 3.5 times or more, a high yield is easily obtained in terms of material balance, the mechanical strength is not decreased, and thickness unevenness in the width direction is not likely to become large, which is preferable. In addition, when the stretching ratio in the width direction is 5.0 times or less, breakage during film formation by stretching is unlikely to occur, which is preferable.

[0072] The biaxial stretching step in the longitudinal and transverse directions is followed by a heat setting step. The heat setting temperature of the film obtained by stretching the unstretched sheet in the longitudinal direction and then stretching the film in the transverse direction is preferably 220°C or higher and 250°C or lower. When the heat setting temperature is 220° C. or higher, the heat shrinkage rate in both the longitudinal and transverse directions is not too high, and the thermal dimensional stability during secondary processing is improved, which is preferable. On the other hand, when the heat setting temperature is 250° C. or less, bowing is unlikely to increase, and variations in molecular orientation and thermal shrinkage rate and distortion in the film width direction are reduced, which is preferable.

[0073] A heat relaxation treatment step is then carried out, which may be carried out separately from the heat setting step after the heat setting step, or may be carried out simultaneously with the heat setting step. The relaxation rate in the film width direction in the heat relaxation treatment step is preferably 4% or more and 8% or less. When the relaxation rate is 4% or more, the heat shrinkage rate in the width direction of the obtained biaxially oriented polyester film is not too high, and the dimensional stability during secondary processing is good, which is preferable. On the other hand, when the relaxation rate is 8% or less, the longitudinal stretching stress caused by the widthwise stretching of the central portion of the film does not become too large, and the bowing phenomenon is less likely to increase, which is preferable.

[0074] In the heat relaxation process, the film obtained by stretching the unstretched sheet in the longitudinal direction is stretched in the width direction, and during the time until the film is shrunk by heat relaxation, the binding force in the width direction is reduced and the film slackens under its own weight, and the film may expand due to the accompanying air currents of the hot air blown from the nozzles installed above and below the film, so the film is in a state in which it is very likely to fluctuate up and down, and the change in the orientation angle of the obtained biaxially oriented polyester film is likely to fluctuate greatly. Methods for reducing these include, for example, adjusting the wind speed of the hot air blown from the nozzles at the top and bottom to keep the film parallel.

[0075] The biaxially oriented polyester film of the present invention may be subjected to a corona discharge treatment, a glow discharge treatment, a flame treatment, or a surface roughening treatment, and may also be subjected to a known anchor coat treatment, printing, decoration, etc., as long as the object of the present invention is not impaired.

[0076] The wide biaxially oriented polyester film stretched by the above method is wound up by a winder device to produce a master roll. The width of the master roll is preferably 5000 mm or more and 10000 mm or less. If the roll width is 5000 mm or more, the cost per film area in the subsequent secondary processing such as slitting, deposition processing, and printing processing is lower, which is preferable. The length of the master roll is preferably 10,000 m or more and 100,000 m or less. If the length of the roll is 5,000 m or more, the cost per film area in the subsequent secondary processing such as slitting, deposition processing, and printing processing is preferably low. The winding width of the film roll slit from the master roll is preferably 400 mm or more and 3000 mm or less. If the winding width is 400 mm or more, the time and effort required for frequent film roll replacement during the printing process is reduced, which is preferable in terms of cost. In addition, the winding width is preferably longer, but if it is 3000 mm or less, the roll width is not too large and the roll weight is not too heavy, which is preferable since handling properties are not reduced. The length of the film roll is preferably 2000 m or more and 65000 m or less. If the length is 2000 m or more, the time and effort required for frequently replacing the film roll during the printing process is reduced, which is preferable in terms of cost. In addition, the longer the length, the better, but if the length is 65000 m or less, the roll diameter will not be too large and the roll weight will not be too heavy, which is preferable since handling properties will not be reduced. The core used for the film roll is not particularly limited, and typically, a cylindrical core made of plastic, metal, or cardboard with a diameter of 3 inches (37.6 mm), 6 inches (152.2 mm), 8 inches (203.2 mm), etc. can be used.

[0077] [Characteristics of biaxially oriented polyester film and film roll] The biaxially oriented polyester film of the present invention made of a polyester resin composition containing a polyester resin recycled from PET bottles and particles preferably satisfies all of the following requirements (1) to (4). Each of these will be described in detail. (1) The temperature-rising crystallization temperature measured by a differential scanning calorimeter (DSC) is 120° C. or higher and 139° C. or lower. (2) The change in orientation angle in the width direction of the film is from 0° to 10° per 0.5 m. (3) When heat-treated at 150°C for 30 minutes across the entire width of the film, the thermal shrinkage is in the range of 0.5% to 2.0% in the longitudinal direction and -1.0% to 1.0% in the transverse direction. (4) The content of the isophthalic acid component relative to 100 mol % of all dicarboxylic acid components in the polyester resin composition is 0.01 mol % or more and 3.0 mol % or less.

[0078] [Heating crystallization temperature (Tc1)] The temperature-induced crystallization temperature of the biaxially oriented polyester film of the present invention is preferably 139° C. or lower, and more preferably 135° C. or lower. The temperature-induced crystallization temperature of polyester resins recycled from PET bottles is usually about 130° C., which is lower than the temperature-induced crystallization temperature of polyester resins derived from fossil fuels. Therefore, if the temperature-induced crystallization temperature in the film is higher than 139° C., it becomes difficult to produce a polyester film with a high ratio of recycled resin, which is not preferable.

[0079] [Change in orientation angle in film width direction] The change in the orientation angle of the biaxially oriented polyester film of the present invention is preferably 0° to 10° per 0.5 m, more preferably 0° to 8°, and even more preferably 0° to 6°. The orientation angle referred to here is the inclination of the main axis of molecular chain orientation when the width direction is used as a reference. If the change in the orientation angle is greater than 10° per 0.5 m, the main molecular orientation direction within the film width is significantly different, so when a film roll made by winding a wide film is used, the running property is deteriorated and wrinkles are likely to occur diagonally during secondary processing such as deposition processing and printing processing, and there is a risk of partial processing spots and processing defects, which may impair the film quality. Here, the sampling positions in the entire width are the center position in the width direction and positions at intervals of 500 mm from the center position toward both ends, and if 500 mm intervals cannot be secured near both ends, the end positions where sampling is possible are used. In addition, the maximum value of each change amount calculated between two adjacent sample sampling positions is within the range, which satisfies the above range.

[0080] [Heat shrinkage rate in the longitudinal and transverse directions] In the entire width of the biaxially oriented polyester film of the present invention, the heat shrinkage rate when heat-treated at 150°C for 30 minutes is preferably in the range of 0.5% to 2.0% in the longitudinal direction and -1.0% to 1.0% in the transverse direction, and more preferably in the range of 0.8% to 1.8% in the longitudinal direction and -0.8% to 0.8% in the transverse direction. By setting the heat shrinkage rate in the longitudinal and transverse directions within the above ranges, dimensional stability against heat is obtained during secondary processing such as deposition processing and printing processing, and there is no occurrence of deformation or wrinkles due to heat, and the film quality is less likely to be impaired, which is preferable. Here, the sampling positions in the entire width are the center position in the transverse direction and positions at intervals of 500 mm from the center position toward both ends, and if 500 mm intervals cannot be secured near both ends, the end positions where sampling is possible are used. In addition, attention is paid to the maximum and minimum values ​​of each measurement position data, and it is considered to be within the range if both of them satisfy the above range.

[0081] [Film thickness] The film thickness of the biaxially oriented polyester film of the present invention is preferably 5 to 40 μm. If it is 5 μm or more, the strength and stiffness of the film will not decrease, and the film roll is less likely to wrinkle when wound by a winder device, which is preferable. On the other hand, if the film thickness is in the range of 40 μm or less, sufficient strength and stiffness can be obtained, and it is preferable to make the film thinner from the viewpoint of cost. The film thickness is more preferably 8 to 30 μm, and particularly preferably 9 to 20 μm. EXAMPLES

[0082] A. The evaluation method for polyester resin is as follows. [Glass transition temperature (Tg)] Using a differential scanning calorimeter (DSC6220, manufactured by SII NanoTechnology Inc.), 5 mg of the resin sample was melted to 280°C under a nitrogen atmosphere, held for 5 minutes, and then rapidly cooled with liquid nitrogen. Measurements were performed at a heating rate of 20°C / min from room temperature.

[0083] [Intrinsic viscosity (IV)] 0.2 g of polyester resin was dissolved in 50 ml of a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (60 / 40 (weight ratio)), and the viscosity was measured using an Ostwald viscometer at 30° C. The unit is dl / g.

[0084] [Content of terephthalic acid and isophthalic acid components in raw polyester and polyester that composes the film] A sample solution was prepared by dissolving chloroform D (Eurisop) and trifluoroacetic acid D1 (Eurisop) in a mixed solvent at a volume ratio of 10:1, and the NMR of the protons in the sample solution was measured using an NMR (GEMINI-200; Varian) at a temperature of 23°C and an accumulation of 64 times. In the NMR measurement, the peak intensity of a specified proton was calculated, and the content (mol %) of the terephthalic acid component and the isophthalic acid component in 100 mol % of the acid component was calculated.

[0085] B. The polyester film was evaluated as follows. Sampling of films for evaluation of properties other than the processability evaluation of the film roll described below was performed from the surface layer of the biaxially oriented polyester film roll of the present invention.

[0086] [Film thickness] The measurement was performed using a dial gauge in accordance with JIS K7130-1999 Method A.

[0087] [Heating crystallization temperature] An 8 mg sample cut from the evaluation film was measured using a differential scanning calorimeter (DSC60) manufactured by Shimadzu Corporation. The sample temperature is (1) Heat up from 25℃ to 320℃ at 10℃ / min (2) Rapid cooling to 25°C at 300°C / min (3) Hold at 25°C for 3 minutes (4) Heat from 25°C to 320°C at 10°C / min The peak top temperature of the heat generation curve of the temperature-promoted crystallization in (4) was determined as the temperature-promoted crystallization temperature (Tc1).

[0088] [Heat shrinkage rate in the longitudinal and transverse directions] A sample was cut out of the evaluation film in a width of 10 mm and a length of 250 mm in the longitudinal and transverse directions, and marks were made at 200 mm intervals. The intervals (A) between the marks were measured under a constant tension of 5 gf. The film was then heat-treated at 150 ° C. for 30 minutes under no load, after which the intervals (B) between the marks were measured under a constant tension of 5 gf, and the thermal shrinkage was calculated using formula (1). The measurements were performed at intervals of 500 mm from the center and the center position toward both ends over the entire width of the obtained biaxially oriented polyester film. In addition, when 500 mm intervals could not be secured near both ends, measurements were performed at measurable end positions. The maximum and minimum values ​​of the thermal shrinkage in the longitudinal and transverse directions over the entire width of the film were calculated based on the thermal shrinkage thus obtained. Heat shrinkage rate (%) = {(AB) / A} × 100 Formula (1)

[0089] [Change in orientation angle in film width direction] The evaluation film was cut to 100 mm x 100 mm, and the orientation angle of the molecular chain main axis was determined using an MOA-6004 molecular orientation meter manufactured by Oji Instruments Co., Ltd., with the axis in the width direction of the film as the reference. At this time, the inclination counterclockwise with respect to the width direction of the film was defined as +, and the inclination clockwise was defined as -. The measurements were performed at intervals of 500 mm from the center and from the center position toward both ends over the entire width of the obtained biaxially oriented polyester film. In addition, when 500 mm intervals could not be secured near both ends, measurements were performed at measurable end positions, and the measurements were divided by the distance between the measured samples and converted to per 0.5 m using formula (2). Change in orientation angle per 0.5m (° / 0.5m) = |Difference in orientation angle between two adjacent points (°)| ÷ Measured sample interval distance (mm) × 500 (mm / m) Formula (2) The maximum value of the calculated changes between two adjacent sample collection positions was taken as the evaluation result of the change in the film.

[0090] [Evaluation of film roll processability and appearance] Gravure printing was performed on the obtained film roll (wound length 60,000 m, width 800 mm) using a gravure printing machine (manufactured by Azumaya Iron Works Co., Ltd.), and the processability of the film during printing and the appearance after processing were evaluated with a grade of ◯ or ×. If there was no sagging or wrinkles and the running property was good, it was rated as ◯. If there was sagging or wrinkles or the running property could not be said to be good, it was rated as ×.

[0091] Details of the raw resin chips used in the present examples and comparative examples are given below. (Polyester resin A): Mechanically recycled polyester resin The mechanically recycled polyester resin made from recycled PET bottles and used in the production of the biaxially oriented polyester film described below was synthesized by the following method. After washing out the remaining beverage and other foreign matter from the PET bottle, the bottle was crushed to obtain flakes. The obtained flakes were washed with 3.5% by weight of sodium hydroxide solution under stirring at a flake concentration of 10% by weight, at 85°C, for 30 minutes. After the alkaline washing, the flakes were taken out and washed with distilled water under stirring at a flake concentration of 10% by weight, at 25°C, for 20 minutes. This water washing was repeated two more times by replacing the distilled water. After washing with water, the flakes were dried, melted in an extruder, and filtered twice more fine foreign matter by changing the filter to a smaller mesh size, and the third time, filtered with a filter with the smallest mesh size of 50 μm to obtain polyester resin A with an intrinsic viscosity of 0.69 dl / g and an isophthalic acid content of 3.0 mol%.

[0092] (Polyester resin B) The fossil fuel-derived PET resin used in the production of the biaxially oriented polyester film described below was terephthalic acid / ethylene glycol=100 / / 100 (mol %) (manufactured by Toyobo Co., Ltd., intrinsic viscosity 0.62 dl / g).

[0093] (Polyester resin C): Chemically recycled polyester resin The chemically recycled polyester resin recycled from PET bottles used in the production of the biaxially oriented polyester film described below was synthesized by the following method. The PET bottles that were collected and sorted were put into a wet grinder, and 1,000 liters of water with 500g of liquid kitchen detergent added was circulated inside the wet grinder while grinding, and metals, sand, glass, and other materials with high specific gravity were precipitated in a gravity separator connected to the grinder, and flakes were taken out from the top layer. These flakes were rinsed with pure water and centrifuged to produce recovered flakes.

[0094] The recovered flakes were melted in a wet state, and 30 kg of the melted flakes were placed in a stirrer-equipped autoclave and charged into a preheated mixture of 150 kg of ethylene glycol and 150 g of zinc acetate dihydrate. After removing fractions with a boiling point lower than that of ethylene glycol, such as water and acetic acid, the mixture was reacted for 4 hours at a temperature of 195-200°C using a reflux condenser.

[0095] After the reaction was completed, the temperature of the contents of the reactor was lowered to 97 to 98° C., and the contents were filtered while still hot to remove suspended matter and precipitates.

[0096] The filtrate after hot filtration was further cooled, and after confirming that the crude BHET was completely dissolved, it was passed through an activated carbon bed at 50 to 51°C and then through an anion / cation exchange mixed bed over 30 minutes for pre-purification treatment.

[0097] The above pre-purified liquid was again charged into the stirring autoclave and heated to distill off excess ethylene glycol under normal pressure, thereby obtaining a molten liquid of concentrated BHET.

[0098] The resulting molten liquid of concentrated BHET was allowed to cool naturally while stirring under a nitrogen gas atmosphere, and then removed from the autoclave to obtain a small block of concentrated BHET.

[0099] The block of fine pieces was again heated to 130°C and melted, then fed to a thin-film vacuum evaporator by a metering pump, evaporated, and cooled and condensed to obtain purified BHET.

[0100] This purified BHET was used as a raw material to carry out melt polymerization, thereby obtaining a chemically recycled polyester resin C having an intrinsic viscosity of 0.696 dl / g.

[0101] (Polyester Resin D) When the temperature of the esterification reactor reached 200°C, a slurry consisting of terephthalic acid [86.4 parts by mass] and ethylene glycol [64.4 parts by mass] was charged, and antimony trioxide [0.017 parts by mass] and triethylamine [0.16 parts by mass] were added as catalysts while stirring. The reactor was then heated to increase the temperature, and a pressurized esterification reaction was carried out under conditions of a gauge pressure of 0.34 MPa and 240°C. Thereafter, the inside of the esterification reactor was returned to normal pressure, and magnesium acetate tetrahydrate [0.071 parts by mass] was added, followed by trimethyl phosphate [0.014 parts by mass]. After the temperature was raised to 260°C over 15 minutes, trimethyl phosphate [0.012 parts by mass] was added, followed by sodium acetate [0.0036 parts by mass]. After 15 minutes, dispersion was performed using a high-pressure disperser, and 0.72 parts by weight of ethylene glycol slurry of amorphous silica particles with an average particle size of 2.7 μm was added based on the particle content. These silica particles are particles obtained by previously preparing an ethylene glycol slurry, centrifuging the slurry to remove 35% of the coarse particles, and then filtering the slurry using a metal filter with an opening of 5 μm. After 15 minutes, the obtained esterification reaction product was transferred to a polycondensation reactor, and polycondensation was performed under reduced pressure at 280°C to obtain a polyester resin D with an intrinsic viscosity of 0.62 dl / g. (Polyester Resin E) When the temperature of the esterification reactor reached 200°C, a slurry consisting of terephthalic acid [86.4 parts by mass] and ethylene glycol [64.4 parts by mass] was charged, and antimony trioxide [0.017 parts by mass] and triethylamine [0.16 parts by mass] were added as catalysts while stirring. The reactor was then heated to increase the temperature, and a pressurized esterification reaction was carried out under conditions of a gauge pressure of 0.34 MPa and 240°C. Thereafter, the inside of the esterification reactor was returned to normal pressure, and magnesium acetate tetrahydrate [0.071 parts by mass] was added, followed by trimethyl phosphate [0.014 parts by mass]. After the temperature was raised to 260°C over 15 minutes, trimethyl phosphate [0.012 parts by mass] was added, followed by sodium acetate [0.0036 parts by mass]. After 15 minutes, dispersion was performed using a high-pressure disperser, and 30.0 parts by weight of ethylene glycol slurry of amorphous silica particles with an average particle diameter of 2.7 μm was added based on the particle content. These silica particles were obtained by previously preparing an ethylene glycol slurry, centrifuging the slurry to remove 35% of the coarse particles, and then filtering the slurry using a metal filter with an opening of 5 μm. After 15 minutes, the obtained esterification reaction product was transferred to a polycondensation reactor, and polycondensation was performed under reduced pressure at 280°C to obtain a polyester resin E with an intrinsic viscosity of 0.61 dl / g.

[0102] The raw resin chips are as shown in Table 1. The abbreviations in the table are as follows: TPA: Terephthalic acid EG: Ethylene glycol

[0103] [Table 1]

[0104] [Example 1] A three-layer film was produced using three extruders. The base layer (B) was 95.0% by mass of polyester resin A and 5.0% by mass of polyester resin D, and the surface layer (A) was 87.5% by mass of polyester resin A and 12.5% ​​by mass of polyester resin D. After drying each raw resin, the mixed resin forming the surface layer (A) was melt-extruded from the first and third extruders at a resin temperature of 285 ° C., and the mixed resin forming the base layer (B) was melted at a resin temperature of 285 ° C. by the second extruder, and the layers were laminated in the order of surface layer (A) / base layer (B) / surface layer (A) from the side contacting the casting drum so that the thickness ratio was 1 / 10 / 1 (μm) in a T-die, extruded from a T-shaped die, and cooled and solidified on a casting drum with a surface temperature of 25 ° C. to obtain an unstretched polyethylene terephthalate sheet. At this time, static electricity was applied using a wire electrode with a diameter of 0.15 mm, and the film was brought into close contact with a cooling drum to obtain a three-layer unstretched film. The obtained unstretched film was heated to 120° C. with an infrared heater and stretched in one step in the longitudinal direction at a stretching ratio of 4.0 times. The film was then stretched in the width direction in a tenter-type transverse stretching machine at a preheat temperature of 120°C, a stretching temperature of 130°C, and a stretch ratio of 4.2 times, and in the cooling zone provided prior to the heat setting zone following the tenter, aluminum plates attached to the top, bottom, left and right sides were used to block hot air, and compressed air was sent in to cool the film down to a temperature of 70°C in the cooling zone. The film was then heat set at 245°C, subjected to 5% thermal relaxation in the width direction, and the surface layer (A) on the side that came into contact with the chill roll was stretched at 40 W·min / m 2 A corona treatment was performed under the above conditions, and the film was wound up into a roll using a winder to produce a master roll (60,000 m long, 8,000 mm wide) of biaxially oriented polyester film with a thickness of 12 μm. The biaxially oriented polyester film was unwound from the obtained master roll and slit into a width of 800 mm onto a core having a diameter of 6 inches (152.2 mm). The film roll was wound up while applying surface pressure to the film roll with a contact roll and tension to the film with a two-axis turret winder. The raw material composition and film-forming conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film are shown in Table 2. The film was evaluated on the surface layer (A) on the side in contact with the chill roll.

[0105] [Example 2] A biaxially stretched film was produced in the same manner as in Example 1, except that the width direction preheating temperature was changed to 105° C., to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film, are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0106] [Example 3] A biaxially stretched film was produced in the same manner as in Example 1, except that the thermal relaxation rate in the width direction was changed to 8%, to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film, are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0107] [Example 4] A biaxially stretched film was produced in the same manner as in Example 1, except that the raw materials were changed to 99.7% by mass of polyester resin A and 0.3% by mass of polyester resin E in the surface layer (A), and 99.88% by mass of polyester resin A and 0.12% by mass of polyester resin E in the base layer (B), to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, the physical properties of the obtained film, and the evaluation results are shown in Table 2. The film was evaluated on the surface of layer A on the side that contacted the chill roll.

[0108] [Example 5] A biaxially stretched film was produced in the same manner as in Example 1, except that the raw materials were changed to 72.2% by mass of polyester resin A and 27.8% by mass of polyester resin D in the surface layer (A), and 72.2% by mass of polyester resin A and 27.8% by mass of polyester resin D in the base layer (B), to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, the physical properties of the obtained film, and the evaluation results are shown in Table 2. The film was evaluated on the surface of layer A on the side that contacted the chill roll.

[0109] [Example 6] A biaxially stretched film was produced in the same manner as in Example 1, except that the polyester resin A used in the surface layer (A) and base layer (B) in Example 1 was changed to a ratio of polyester resin A / polyester resin C = 50 / 50 as the raw material, to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, and the physical properties and evaluation results of the obtained film are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0110] [Example 7] A biaxially stretched film was produced in the same manner as in Example 1, except that the polyester resin A used in the surface layer (A) and base layer (B) in Example 1 was changed to a ratio of polyester resin A / polyester resin C = 10 / 90, to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film, are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0111] [Example 8] A biaxially stretched film was produced in the same manner as in Example 1, except that polyester resin A was used for the surface layer (A) and polyester resin C was used for the base layer (B), to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film, are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0112] [Example 9] A biaxially stretched film was produced in the same manner as in Example 1, except that polyester resin C was used for the surface layer (A) and polyester resin A was used for the base layer (B), to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film, are shown in Table 2. The film was evaluated on the surface layer (A) on the side that came into contact with the chill roll.

[0113] [Comparative Example 1] A biaxially stretched film was produced in the same manner as in Example 1, except that the polyester resin of the surface layer (A) was changed to polyester resin B as the raw material, the longitudinal stretching temperature was changed to 130° C., the width direction preheating temperature was changed to 130° C., and the width direction stretching temperature was changed to 140° C., to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, and the physical properties and evaluation results of the obtained film are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0114] [Comparative Example 2] A biaxially stretched film was produced in the same manner as in Example 1, except that no cooling zone was provided before the heat setting zone in the biaxial stretching step, to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film, are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0115] [Comparative Example 3] A biaxially stretched film was produced in the same manner as in Example 1, except that the cooling zone temperature was changed to 50°C before the heat setting zone, to obtain a biaxially oriented polyester film having a thickness of 12 µm. The raw material composition and film production conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film, are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0116] [Comparative Example 4] A biaxially stretched film was produced in the same manner as in Example 1, except that the transverse stretching temperature was changed to 145° C., to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film, are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0117] [Comparative Example 5] As raw materials, the surface layer (A) had 91.7% by mass of polyester resin A and 8.3% by mass of polyester resin C, the base layer (B) had 91.7% by mass of polyester resin A and 8.3% by mass of polyester resin C, the longitudinal stretching temperature was changed to 115°C, the widthwise stretching temperature was changed to 115°C, the heat setting temperature was changed to 235°C, preheating in the widthwise direction was not performed, and a cooling region was not provided before the heat setting region. A biaxially stretched film was produced in the same manner as in Example 1 to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film-forming conditions of the obtained film, the physical properties of the obtained film, and the evaluation results are shown in Table 2. The film was evaluated on the surface of layer A on the side in contact with the chill roll.

[0118] [Table 2A]

[0119] [Table 2B]

[0120] [Table 2C]

[0121] As shown in the results of Table 2, the films of Examples 1 to 5 had the heating crystallization temperature, the change in orientation angle in the width direction, the thermal shrinkage rate in the longitudinal and width directions across the entire width, and the content of isophthalic acid component within the specified ranges, so that the films had little variation or distortion in the molecular orientation and thermal shrinkage rate in the width direction of the film and had uniform physical properties in the width direction of the film, making them suitable for various processing applications, and were environmentally friendly biaxially oriented polyester films using polyester resin recycled from PET bottles.

[0122] In Comparative Example 1, the change in orientation angle in the width direction of the obtained film and the thermal shrinkage rates in the longitudinal and width directions over the entire width were within the specified ranges, making it suitable for various processing applications. However, since the film was made of a conventional polyester resin derived from fossil fuels and had a low content of isophthalic acid components, it was inferior as an environmentally friendly polyester film.

[0123] In Comparative Example 2, a cooling region was not provided before the heat setting treatment region, and although the heating crystallization temperature, the thermal shrinkage rate in the longitudinal and transverse directions across the entire width, and the content of isophthalic acid component were within the specified ranges, the change in orientation angle in the transverse direction was large, and the film processability evaluation was poor.

[0124] In Comparative Example 3, the heating crystallization temperature, the change in orientation angle in the width direction, and the content of isophthalic acid component of the obtained film were within the specified ranges, but the heat shrinkage rates in the longitudinal and width directions over the entire width were outside the specified ranges, and the film processability was evaluated as poor due to poor dimensional stability against heat.

[0125] In Comparative Example 4, the heating crystallization temperature, the change in orientation angle in the width direction, the thermal shrinkage rate in the longitudinal and width directions over the entire width, and the content of isophthalic acid component were all within the specified ranges. However, the temperature during width direction stretching was high, making the film prone to breakage during stretching film formation. As a result, it was not possible to stably obtain a master roll with a winding length of 60,000 m, and the film was inferior as a film roll for industrial continuous production.

[0126] In Comparative Example 5, the heating crystallization temperature, the thermal shrinkage rate in the longitudinal and transverse directions across the entire width, and the content of isophthalic acid component were within the specified ranges, but the change in orientation angle in the transverse direction was large, so the film processability evaluation was poor. [Industrial Applicability]

[0127] The biaxially oriented polyester film of the present invention has little variation in molecular orientation and thermal shrinkage rate and distortion in the width direction of the film, and the physical properties in the width direction of the film are uniform, making it suitable for a variety of processing applications.In addition, by using polyester resin made from recycled PET bottles, it is possible to provide an environmentally friendly biaxially oriented polyester film and a manufacturing method thereof. This technology can be widely used in the field of packaging films, such as food packaging and gas barrier films, and is expected to make a significant contribution to the industrial sector, as there is a strong desire in recent years to reduce the environmental impact.

Claims

1. A biaxially oriented polyester film made of a polyester resin composition containing a polyester resin recycled from polyethylene terephthalate containers and particles, the biaxially oriented polyester film having an outermost layer A and a central layer B, at least layer A containing a polyester resin recycled from polyethylene terephthalate containers and particles, and satisfying all of the following requirements (1) to (4): (1) The heating crystallization temperature measured by a differential scanning calorimeter (DSC) is 120° C. or higher and 139° C. or lower. (2) The change in orientation angle in the film width direction is 0° or higher and 10° or lower per 0.5 m. (3) When the film is heat-treated at 150°C for 30 minutes, the heat shrinkage is in the range of 0.5% to 2.0% in the longitudinal direction and -1.0% to 1.0% in the transverse direction in the entire width of the film. (4) The content of isophthalic acid components relative to 100 mol% of all dicarboxylic acid components in the polyester resin composition is 0.01 mol% to 3.0 mol%. Here, the sampling positions in requirements (2) and (3) are the center position and positions at intervals of 500 mm from the center position toward both ends of the entire width, and if 500 mm intervals cannot be secured near both ends, the edge positions where sampling is possible are used. In addition, requirement (2) requires that the maximum and minimum values ​​of each measurement position data are within a range, and requirement (3) requires that the maximum value of each change between two adjacent sample sampling positions is within a range.

2. The biaxially oriented polyester film according to claim 1, characterized in that the content of polyester resin recycled from polyethylene terephthalate containers in the polyester resin composition constituting the biaxially oriented polyester film is 50% by mass or more and 100% by mass or less.

3. 3. The biaxially oriented polyester film according to claim 1, wherein the polyester resin recycled from the polyethylene terephthalate container is a mechanically recycled polyester resin and / or a chemically recycled polyester resin.

4. A method for producing a biaxially oriented polyester film according to any one of claims 1 to 3, comprising a polyester raw material resin melt extrusion step, a biaxial stretching step, a heat setting step, a heat relaxation step, and a step of winding up the biaxially oriented polyester film into a roll, characterized in that in the biaxial stretching step, after the film is stretched in the longitudinal direction, it is stretched in the width direction in a tenter, and a cooling zone is provided before the heat setting zone.

Citation Information

Patent Citations

  • Biaxially oriented polyester film and its manufacture

    JP1997295345A

  • Polyester film

    JP2014080595A

  • Laminated film

    JP2019077193A

  • Laminated film

    KR1020130003505A

  • Steam iron

    JP1985036099A